Multi-criteria routing metric for supporting data-differentiated service in hybrid wireless mesh networks in coal mines - Liansheng Lu; Haifeng Jiang; Guangzhi Han; Shanshan Ma; Renke Sun (International Journal of Distributed Sensor Networks)
Mesh clients in hybrid wireless mesh networks can perform the routing functionality, as well as provide end-user applications that are more suitable for tunnels, to improve the connectivity of backbone networks. In this article, based on the diversity of data and limited power supply of mesh clients in hybrid wireless mesh networks in underground mines, we propose a multi-criteria routing metric to support data-differentiated service. This routing metric divides data into two types: urgent and non-urgent. End-to-end delay is calculated when transmitting urgent data, and hop count and link load are measured when transmitting non-urgent data. In order to optimize the utilization of mesh clients and to prolong the network lifetime, mesh clients and mesh routers are given different weights in the calculation of hop count. Based on the QualNet7.1 simulation platform, the performance of the proposed routing metric in transmitting urgent and non-urgent data is evaluated through numerous simulations. Simulation results indicate that the routes selected using the proposed routing metric can effectively reduce the average end-to-end delay when transmitting urgent data and reduce the utilization rate of mesh clients while simultaneously guaranteeing the capability of the network when transmitting non-urgent data. This finding satisfies the differentiated service requirements of data of different types for hybrid wireless mesh networks in coal mines.